Navigating Digital Competence in TVET Education: Overcoming Challenges and Harnessing Opportunies for Industry 4.0 - Mohd Rokeman, Nor Roselidyawaty; Che Kob, Che Ghani; Othman, Farah Waheda; Che Sobry, Hanzolah; Mohd Raffi, Mohd Lutfi; Mohd Nong, Siti Aisyah; Untong, Mohd Fadzlee; Mohd Yaacob, Mohd Nasir (Jurnal Pendidikan Bitara UPSI, 2024)
The significance of digital skills in Technical and Vocational Education and Training (TVET) is increasing as technology plays a more prominent role in businesses and employment. This scoping review aims to address a knowledge gap suggesting that digital education requires adjustments in pedagogy and evaluation, necessitating instructor training and professional development. Thematic analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Themes from Scopus repositories and Google Scholar were extracted and analysed using specific keywords related to digital literacy topics. After the search, a total of n = 16 domains were initially identified and analysed comprehensively. Two themes emerged from the analysis: (1) Challenges, and (2) Strategies to overcome the digital competence challenges. The findings highlight a variety of approaches and technologies relevant to digital competency concerns. The review reveals gaps in the current literature and proposes future research directions to explore the potential and challenges associated with the benefits of training in TVET education. In conclusion, the thematic analysis provides valuable insights for educators, scholars, and policymakers to develop effective strategies for fostering digital proficiency in TVET programs. These strategies involve revising curriculum materials, enhancing instructor training, collaborating with researchers, and integrating digital competency into TVET programs.